Transoral and combined transoral-transcervical approach in the surgery of parapharyngeal tumors - Betka, Jan; Chovanec, Martin; Klozar, Jan; Taudy, Milos; Plzák, Jan; Kodetová, Dana; Lisý, Jirí (European archives of oto-rhino-laryngology, 2010)
The goal of parapharyngeal space (PPS) tumor surgery is to obtain adequate visualization to ensure complete removal with preservation of the surrounding nerves and vessels. Different surgical approaches have been described. Transoral approach is the most controversial one due to cited limited exposure, risk of tumor spillage, and possibility of neurovascular injury. We performed retrospective analysis of 26 consecutive patients who had undergone transoral or combined transoral-transcervical resection of PPS tumors from January 1997 to December 2007. Both approaches were safely employed to remove selected PPS tumors. Majority of treated tumors were pleomorphic adenomas (14 minor salivary gland and 7 deep lobe parotid gland tumors). Two cases of malignant salivary gland tumors, 4 nerve sheath tumors and 1 lymphangioma were also excised. Mean tumor size was 6.1 cm (range 2-11 cm). Visualization was felt to be adequate and dissection safe. Radical resection was achieved in 24 cases. Near-total resection was achieved in two cases where otherwise other approach would be suitable but cannot be undertaken because of patient refusal and comorbidities. Patients with malignant tumors had postoperative radiotherapy. Radically treated cases are disease free. One of the near-totally resected tumors needed revision surgery. Neither major complications nor disordered healing were observed. Transoral approach provides access to selected cases of PPS tumors based on preoperative imaging methods and fine-needle aspiration cytology. Risk of non-radical resection is acceptable. It can be combined with external approach to achieve safe resection of some benign tumors which would need transmandibular approach.
Keywords: nádory slinných žláz; Otorhinolaryngologic Surgical Procedures; mužské pohlaví; nádory hltanu; Neoplasm Staging; ženské pohlaví; Neck; Humans; krk; Mouth; Pharyngeal Neoplasms; Salivary Gland Neoplasms; ústa; otorinolaryngologické chirurgické výkony; staging nádorů; nádory nervové pochvy; Female; Nerve Sheath Neoplasms; lidé; Male